Credit Derivatives : Systemic Risks and Policy Options? - Kiff, John (IMF Working Papers; Working Paper ;, 2009)
Credit derivative markets are largely unregulated, but calls are increasingly being made for changes to this "hands off" stance, amidst concerns that they helped to fuel the current financial crisis, or that they could be a cause of the next one. The purpose of this paper is to address two basic questions: (i) do credit derivative markets increase systemic risk; and (ii) should they be regulated more closely, and if so, how and to what extent? The paper begins with a basic description of credit derivative markets and recent events, followed by an assessment of their recent association with systemic risk. It then reviews and evaluates some of the authorities' proposed initiatives, and discusses some alternative directions that could be taken.